Multioutput least square SVR-based multivariate EWMA control chart: The performance evaluation and application. Issue 1 (1st January 2018) - Khusna, Hidayatul; Mashuri, Muhammad; Suhartono, Suhartono; Prastyo, Dedy Dwi; Ahsan, Muhammad
Abstract: Autocorrelation leads to a bias estimator of standard control charts. It is important to develop control chart that allows autocorrelation and to evaluate its performance. The objective of this paper is to evaluate the performance of multioutput least square support vector regression (MLS-SVR)-based multivariate exponentially weighted moving average (MEWMA) control chart for monitoring multivariate autocorrelated data. For first order of vector autoregressive (VAR) and first order of vector moving average data, the proposed control chart tends to yield stable in-control average run length at about 200. The proposed control chart becomes more insensitive due to the increase of MEWMA smoothing parameter. In the real application, the proposed method is successfully applied to monitor water turbidity and chlorine residual data in the drinking water manufacturing process.